(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this work is to evaluate evidences of a prefix alternance ∅- / t- in Iberian language and, in a secondary level, to analyze eventual relationship between this alternance and feminine formation procedures.